A review of the Siyakhula Living Lab's network solution for Internet in marginalized communities - Muchatibaya, Hilbert Munashe (Rhodes University, Faculty of Science, Department of Computer Science)
Changes within Information and Communication Technology (ICT) over the past decade required a review of the network layer component deployed in the Siyakhula Living Lab (SLL), a long-term joint venture between the Telkom Centres of Excellence hosted at University of Fort Hare and Rhodes University in South Africa. The SLL overall solution for the sustainable internet in poor communities consists of three main components "“ the computing infrastructure layer, the network layer, and the e-services layer. At the core of the network layer is the concept of BI, a high-speed local area network realized through easy-to deploy wireless technologies that establish point-to-multipoint connections among schools within a limited geographical area. Schools within the broadband island become then Digital Access Nodes (DANs), with computing infrastructure that provides access to the network. The review, reported in this thesis, aimed at determining whether the model for the network layer was still able to meet the needs of marginalized communities in South Africa, given the recent changes in ICT. The research work used the living lab methodology "“ a grassroots, user-driven approach that emphasizes co-creation between the beneficiaries and external entities (researchers, industry partners and the government) - to do viability tests on the solution for the network component. The viability tests included lab and field experiments, to produce the qualitative and quantitative data needed to propose an updated blueprint. The results of the review found that the network topology used in the SLL's network, the BI, is still viable, while WiMAX is now outdated. Also, the in-network web cache, Squid, is no longer effective, given the switch to HTTPS and the pervasive presence of advertising. The solution to the first issue is outdoor Wi-Fi, a proven solution easily deployable in grass-roots fashion. The second issue can be mitigated by leveraging Squid's 'bumping' and splicing features; deploying a browser extension to make picture download optional; and using Pihole, a DNS sinkhole. Hopefully, the revised solution could become a component of South African Government's broadband plan, "SA Connect" .
Keywords: Information and communication technologies for development; Information technology -- South Africa; Access network; User experience; Local area networks (Computer networks) -- South Africa